Full genomic sequence of the HLA‐DRB3*02:32 allele by Single Molecule Real‐time Sequencing Technology. (13th November 2022) - Liacini, Abdelhamid; 't Hart, Daan C.; Peters, Lindsey; Persidsky, Yuri; Geier, Steven
Abstract : Full‐length sequence covers the 5′‐untranslated region (UTR), all introns and exons and the 3′ UTR.